Um estudo sobre as exportações chilenas a partir das reformas liberalizantes dos anos 1970 - Mussa, Luciano (2006)
This research analyzes the exporting performance of Chile since the great changes introduced in its economy after the military blow of 1973. The Chilean exports had grown a lot in this period, with important diversification of products and participant companies, and are pointed as one of the main responsible for the vigorous growth of the economy since middle of years 1980's. The analysis here developed presents elements to evaluate in what extend and how the exporting peak contributed for the positive performance of the Chilean economy. There are adopted three approaches for the relation between exports and growth: i) the contribution of the exports for the productivity rise and technology incorporation; ii) the sustentation of favorable position in the balance of payments; iii) the sustentation of the aggregate demand. The analysis detaches the relatively steady performance of the exports in relation to the product, one of the elements that had contributed for the good macroeconomic performance, for having contributed to reduce the risks of problems in the balance of payments, since the solution of the serious crisis of 1981-1983, beyond having contributed to keep high the chain of imports throughout the period. More controversial is the effect of the exporting peak concerning productivity gains and the incorporation of technological progress. Another important aspect to be verified is the role of the politics used by the State in the vigorous exporting peaks. The initiatives of the government, still during the dictatorship, had contributed a lot for the exporting impulse, question in general neglected by the regular vision of Chile as example of drastic reduction of the state intervention